2018
DOI: 10.3168/jds.2017-13159
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic group, antimicrobial susceptibility, and virulence genes of Escherichia coli from clinical bovine mastitis

Abstract: Bovine mastitis is still a central problem on dairy farms despite control programs, and Escherichia coli is a crucial pathogen during the development of bovine mastitis. The virulence genes, antimicrobial susceptibility, and mortality of mice infected with different E. coli isolates from bovine mastitis were determined in this study. According to the presence of the specific genes chuA, yjaA, and TspE4.C2, these isolates mainly belonged to 2 different groups: group A (47/79) and group B1 (22/79). The ompC gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
47
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 46 publications
(48 reference statements)
15
47
7
2
Order By: Relevance
“…However, only 10Á0% of the isolates were classified as pathogenic phylogroups B2 (6Á0%) and D (4Á0%) (Clermont et al 2011). This finding is in accordance with previous studies that evaluated E. coli isolates phylogenetically from intramammary infections in dairy cattle and predominantly classified strains as commensal or opportunistic pathogens both for humans and domestic animals (Burvenich et al 2003;Fernandes et al 2011;Suojala et al 2011;Blum and Leitner 2013;Zhang et al 2018). Thus, due the lack of association between the specific VFs and the clinical manifestations, the pathogenic actions of E. coli have been partially attributed to concurrent immunosuppressive factors (i.e.…”
Section: Phylogenetic Classificationsupporting
confidence: 91%
See 1 more Smart Citation
“…However, only 10Á0% of the isolates were classified as pathogenic phylogroups B2 (6Á0%) and D (4Á0%) (Clermont et al 2011). This finding is in accordance with previous studies that evaluated E. coli isolates phylogenetically from intramammary infections in dairy cattle and predominantly classified strains as commensal or opportunistic pathogens both for humans and domestic animals (Burvenich et al 2003;Fernandes et al 2011;Suojala et al 2011;Blum and Leitner 2013;Zhang et al 2018). Thus, due the lack of association between the specific VFs and the clinical manifestations, the pathogenic actions of E. coli have been partially attributed to concurrent immunosuppressive factors (i.e.…”
Section: Phylogenetic Classificationsupporting
confidence: 91%
“…; Blum and Leitner ; Zhang et al . ). Thus, due the lack of association between the specific VFs and the clinical manifestations, the pathogenic actions of E. coli have been partially attributed to concurrent immunosuppressive factors (i.e.…”
Section: Resultsmentioning
confidence: 97%
“…(18.5%) in 497 raw milk samples. The prevalence of E. coli isolates was higher in our study than in a study performed in Turkey (3.2%, 8/250) (Akkaya, Cetinkaya, Alisarli, Telli, & Gök, 2008) and in Liaoning province, China (20.1%,79/389) (Zhang et al, 2018). Our results revealed that E. coli is prevalent in raw milk from mastitic cows in all five regions of China.…”
Section: Discussioncontrasting
confidence: 64%
“…Bovine mastitis, which affects dairy farms throughout the world, reduces milk production, negatively impacts milk quality, and represents a source of contamination for raw milk and dairy products (Halasa, Huijps, Østerås, & Hogeveen, 2007). Several bacteria cause mastitis in dairy cows, including Escherichia coli (Olde Riekerink, Barkema, Scholl, Poole, & Kelton, 2010), one of the most predominant pathogens (Zhang et al, 2018), Staphylococcus aureus (Olde Riekerink, Barkema, Kelton, & Scholl, 2008), and Streptococcus uberis (Levison et al, 2016). E. coli, which has an isolation rate of 10.2% in bovine mastitis (Tenhagen, Hansen, Reinecke, Heuwieser, & Lam, 2009), can be classified into pathogenic and nonpathogenic bacteria, and pathogenic bacteria can be further classified into different types based on the pathogenic mechanism (Blum & Leitner, 2013)and virulence factor, such as enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), Shiga toxin-producing E. coli (STEC or VTEC), and enterohemorrhagic E. coli (EHEC (Fitzhenry et al, 2002;Nagy & Fekete, 1999)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation